2020
DOI: 10.5114/amsad.2020.97101
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal atrial fibrillation: changes in factor VIII and von Willebrand factor impose early hypercoagulability

Abstract: Introduction Paroxysmal atrial fibrillation (PAF) is a well-documented prothrombotic state that carries significant embolic risk. However, precise hemostatic changes in the very early stage of the disease are not completely studied. The aim of the study was to study von Willebrand factor (vWF) and coagulation factor VIII (FVIII) plasma levels and activity in the first hours (up to 24 h) of PAF clinical manifestation. Material and methods We selected consecutively 51 non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The origin of both and the role in AF progression remains unknown, but the postulated enhanced potential of tissue factor stimulated coagulation, due to lower TFPI activity, by itself would be in accordance with a role of hypercoagulability in driving AF as previously shown in preclinical studies 9. Recently, it was shown that duration of PAF was associated with higher levels of von Willebrand factor and factor VIII 26. Clearly, more research is warranted on the role of hypercoagulability in AF progression.…”
Section: Discussionmentioning
confidence: 71%
“…The origin of both and the role in AF progression remains unknown, but the postulated enhanced potential of tissue factor stimulated coagulation, due to lower TFPI activity, by itself would be in accordance with a role of hypercoagulability in driving AF as previously shown in preclinical studies 9. Recently, it was shown that duration of PAF was associated with higher levels of von Willebrand factor and factor VIII 26. Clearly, more research is warranted on the role of hypercoagulability in AF progression.…”
Section: Discussionmentioning
confidence: 71%
“…Fourteen studies examined platelet count in AF and controls (868 AF patients, 2269 controls, mean age 62.6 years, 39.5% women). 50,52,56,64,68,69,71,74,[76][77][78][79][80][81] The mean platelet count in AF patients was 235 × 10 9 /l (range 174-277 × 10 9 /l), and 225 × 10 9 in controls (range 212-270 × 10 9 ). Pooled, we found no significant difference between the two groups (SMD −0.41, 95% CI −1.42 to 0.59).…”
Section: Platelet Countmentioning
confidence: 99%
“…In humans, AF is associated with a reduced quality of life and increased morbidity and mortality due to several factors, including atrioventricular dyssynchrony, progressive cardiac dysfunctions and altered hemodynamics [20,107]. Unlike horses, humans with pAF are at increased risk of stroke due to reduced atrial systole and increased atrial stasis [108], while pAF also initiates an early state of hypercoagulability [109]. A study investigating hypercoagulability in horses with AF could not support findings from human studies [110].…”
Section: Treatment 71 Human Treatment Strategiesmentioning
confidence: 99%